PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP PEMAHAMAN KONSEP BIOLOGI DAN KETERAMPILAN BERPIKIR KRITIS SISWA TENTANG EKOSISTEM DAN LINGKUNGAN DI KELAS X SMA NEGERI 1 SIGI - Kono, Rahmad (JSTT, 2016)
The research aimed at investigating the effect of model of  problem based learning (PBL) on the concept comprehension and critical thinking skill about  ecosystem and environment of class X students’ of biology at SMA Negeri 1 Sigi. The method used is quasi-experimental pretest-posttest 2 x 2. The research sample is determined with random sampling. The class selected as the research sample was class X A and X B. The data was collected by using the concept comprehension test in form of  multiple and  the critical thinking skill test in form of essay test. Data obtained was the primary data which directly analyzed descriptively and analysis of covariance. Resuts of the data analysis at significance level α = 0,05 is at follow: (1) the learning outcomes (the concept comprehension) of student that were learned by the model of problem based learning (PBL) (mean=72,86) was higher than the cognitive learning outcomes of studens that were learned with the conventional learning (mean=58,93) with a significance value of  0,003.  (2) the learning outcomes (critical thinking skill) of student that were learned by the model of  problem based learning (PBL) (mean=74,12) was higher than the cognitive learning outcomes of studens that were learned with the conventional learning (mean=57,45) with a significance value of 0,018.  Based on the result of  this research, it can be concluded that: there are the effect  of model of  problem based learning (PBL) on the concept comprehension and critical thinking skill about   ecosystem and environment of  class X students’ of biology at  SMA Negeri 1 Sigi.